Efektivitas Greenpeace Sebagai INGO Lingkungan Dalam Menangani Deforestasi Hutan Amazon di Brazil Tahun 2018-2021 - Muhammad Alif Firdaus; Devita Prinanda (Jayapangus Press, 2022)
Deforestation of the Amazon that has occurred for decades continues to increase every year and presents a real threat. Greenpeace as an environmental INGO also participates in dealing with the deforestation case by making various efforts. The purpose of this study is to explain the effectiveness of Greenpeace in dealing with cases of deforestation in the Amazon Forest in Brazil in 2018-2021. In this study, the author uses the theory of INGO effectiveness and the concept of environmentalism. The analysis in this study uses a qualitative descriptive method with document research data collection techniques. The results of this study indicate that the efforts that have been made by Greenpeace have an impact on the condition of deforestation in the Amazon forest. The effort to monitor the Amazon forest with indigenous peoples is part of the All Eyes on the Amazon project which involves several parties and various advanced technologies. This supervision narrows the space for illegal activities so that by 2020 there will be a reduction in the rate of deforestation by 62 percent on the customary lands of the Karipuna people. However, this decrease has only a small impact considering that the customary land area is only 3.83 percent of the total area of ​​the Amazon forest and there will be an increase in deforestation again in 2021. Based on this, it can be concluded that Greenpeace has not been effective in dealing with the deforestation of the Amazon Forest.